In-Vitro Alpha Amylase Inhibition and Antioxidant Activities of Leaves Extract of Sundanese Traditional Salad (Lalapan) from Indonesia - Wahyuni, Leny Eka Tyas; Hardinsyah, Hardinsyah; Setiawan, Budi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This research aims to evaluate the α-amylase inhibitory activity and antioxidant potential of leaves extract of Gandaria (Bouea macrophylla Griff.), Basil (Ocimum africanum Lour.), Pohpohan (Pilea melastomoides (Poir.) Wedd.), and Lettuce (Lactuca sativa L.) as common vegetables used in Sundanese traditional salad. Extraction methods used were traditional and maceration methods. Phytochemical screening was used to determine the phytochemical component qualitatively. Quantitative estimation of phenols (Folin-Ciocalteu method), flavonoids (AlCl3 colorimetric assay), total antioxidant activity along with free radical scavenging activity (DPPH) was also carried out. Soluble starch was used as substrate for analysis of α-amylase inhibitory activity, which is calculated by IC50 value. Phytochemical screening revealed the presence of phytochemical constituents like flavonoids, tannins, saponins, and polyphenols compound in both extraction methods. The results showed that the value of Total Phenolic Content (TPC), Total Flavonoid Content (TFC), antioxidant activity, and α-amylase inhibitory in both extraction were significantly different for each leaves extracts (p<0.05). The gandaria leaves extracted with maceration method had the highest value among the leaves analysed. The value of TPC, TFC, antioxidant activity were 364.56±65.97 mg Gallic Acid Equivalent (GAE)/g extract, 70.2±10.54 mg Quercetin (QE)/g extract, and 35 µg/ml of IC50, respectively. The extract of gandaria maceration leaves exhibited significant α-amylase inhibitory activity with an IC50 value of 60 µg/ml. Various pharmacologically active compounds were found in the local vegetables, thus they can be rich sources of antioxidants and α-amylase inhibitor activity. Hence, could be developed as vegetables based functional food products.